PEMAHAMAN PETANI GARAM TENTANG KEHALALAN PRODUK DI GAMPONG CEBREK KECAMATAN SIMPANG TIGA KABUPATEN PIDIE - Mahlil, Mahlil; Akram, Nailul (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2019)
This study raised the issue of understanding salt farmers about the halal products starting from pre-production, production processes, and post-production in Gampong Cebrek, Kecamatan Simpang Tiga, Pidie District. The purpose of this research is to find out the understanding of salt farmers about the halal nature of the product and what are the constraints of salt farmers related to efforts to manage product halal guarantee. This study uses a qualitative method with a descriptive approach, and uses a sample selection technique with the provisions of the characteristics and characteristics of objects in a purposive sampling study, the data collection technique is done in three ways, namely observation, interviews, and documentation. The informants were four salt farmers and keuchik Gampong (village head) Cebrek. The results showed that the understanding of salt farmers in terms of pre-production was good, the production process was quite good and post-production was good. The obstacle factor of salt farmers related to product halal guarantee is that the income and expenditure of salt farmers are not comparable or still low so it is not enough to carry out the halal label management process, and is also constrained in the fencing of salt fields. Here there needs to be attention and role from the government, LPPOM (Institute of Studies, Food, Medicine and Cosmetics)-MPU (Ulama Consultative Assembly) Aceh to guide salt farmers to immediately fence off their salt fields so that the salt production process is better so that it meets the standards halal products.Keywords: Understanding of salt farmers, halal products.